Genetic methods in the study of neurological diseases: the genetic basis of neurological disorders - Bras, Jose Miguel (Henry Stewart Talks, 2014)
Historical approaches to genetic studies, Genome-Wide Genotyping, Genome-Wide Association Studies, Next-Generation Sequencing, How we use novel technologies to understand the genetic architecture of disease